The Role of Brand Image Mediates the Effect of Product Quality on Repurchase Intention - Ni Putu Atik Ekayani; Tjokorda Gde Raka Sukawati; Ni Nyoman Kerti Yasa (International Journal of Asian Business and Management, 2024)
Repurchase deliberate may be a consumer's purposeful to purchase a item based on encounter from acquiring and utilizing the past item. A few variables that can cultivate repurchase eagerly are brand picture and item quality. This ponder pointed to clarify the part of brand picture in interceding the impact of item quality on repurchase eagerly among customers of Kulo Coffee Shop. This investigate was conducted in Denpasar City; the number of tests in this consider was 120 respondents utilizing the purposive inspecting strategy. Information collection was carried out by conveying surveys offline and online.  The information investigation strategies utilized are way examination, Sobel test and VAF test. Based on the comes about of the examination, this ponder appears that item quality features a positive and significant impact on repurchase purposeful, item quality incorporates a positive and noteworthy impact on brand picture, brand picture includes a positive and critical impact on repurchase deliberate, brand picture emphatically and altogether intercedes the impact of item quality on repurchase purposeful